Carbon-coated lithium manganese iron phosphate nano material as well as preparation method and application thereof

By forming a floating island structure of carbon-coated and polyanionic sodium ion battery positive electrode material on the surface of lithium manganese iron phosphate nanomaterials, the conductivity and stability of lithium manganese iron phosphate are solved, and the lithium ion transmission rate and cyclic stability are improved , significantly improves the application performance of materials.

CN119133381APending Publication Date: 2024-12-13TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411057681.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The poor electronic conductivity of lithium manganese iron phosphate positive electrode material, low lithium ion transmission rate and poor cycle stability, limit its application in the field of large-scale energy storage.

Method used

Carbon-coated lithium manganese iron phosphate nanomaterials, and a discontinuous polyanionic sodium ion battery positive electrode material floating island structure is formed on its surface, and a close-bonded lattice coherence is used to form a material such as vanadium sodium phosphate and vanadium oxygen sodium phosphate. Structure, improve cycle stability, and accelerate lithium ion transmission through carbon conductivity and structural loose porosity.

Benefits of technology

The cycling stability and lithium ion transmission rate of lithium manganese iron phosphate are significantly improved, the capacity attenuation during charging and discharging is delayed, and the specific capacity retention rate of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133381A_ABST
    Figure CN119133381A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-coated lithium manganese iron phosphate nano material as well as a preparation method and application thereof. The invention provides a polyanionic sodium ion battery positive electrode material and carbon composite coated lithium manganese iron phosphate, the surfaces of lithium manganese iron phosphate nanoparticles have discontinuous floating island structures, and the floating island structures are the polyanionic sodium ion battery positive electrode material. The polyanionic sodium-ion battery positive electrode material has good cycle stability, and can inhibit the dissolution of Mn element, thereby improving the cycle stability. The carbon material coated on the surface of the nano material has good electronic conductivity, and in addition, the structure is loose and porous, so that electrolyte can be adsorbed on the surfaces of lithium manganese iron phosphate particles through capillary action, and the lithium ion transmission rate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano material preparation, and in particular to a carbon-coated lithium manganese iron phosphate nano material and a preparation method and application thereof. Background Art

[0002] In recent years, lithium iron phosphate materials have been widely used in new energy electric vehicles and large-scale energy storage equipment due to their advantages such as high safety, good stability and low cost. However, the voltage of lithium iron phosphate materials is relatively low (3.4V, vs Li + / Li), resulting in its energy density (578Wh / Kg) being uncompetitive compared to other positive electrode materials.

[0003] By replacing part of the Fe element in lithium iron phosphate with Mn, lithium manganese iron phosphate positive electrode material can be obtained. The voltage of lithium manganese iron phosphate can reach 4.1V (vs Li + / Li), the energy density is 10-20% higher than that of lithium iron phosphate, and it is expected to replace lithium iron phosphate in the field of large-scale energy storage in the future.

[0004] However, lithium iron manganese phosphate is essentially a semiconductor with poor electronic conductivity and low lithium ion transfer rate. During the charge and discharge process, the Mn element dissolves; in addition, the Mn element also has the Jahn-Teller effect, which makes the lattice of lithium iron manganese phosphate easily damaged, resulting in its poor cycle stability. Solving the poor electronic conductivity, lithium ion transfer rate and cycle stability of lithium iron manganese phosphate positive electrode materials is the key to further promote its use.

[0005] When the current carbon-coated lithium manganese iron phosphate material is used as a positive electrode material, although it can alleviate the phenomenon of Mn dissolution during the charge and discharge process to a certain extent, in order to ensure the processing performance of lithium manganese iron phosphate in the actual production process, the carbon content in the final sample needs to be controlled within the range of 2-3%wt. Therefore, the lower carbon content cannot fully solve the problem of poor stability of lithium manganese iron phosphate materials. At the same time, the addition of carbon is conducive to improving the electronic conductivity of lithium manganese iron phosphate materials, but the improvement of lithium ion transmission rate is small. Therefore, a coating layer that can effectively improve the cycle stability of lithium manganese iron phosphate materials during charging and discharging and increase the lithium ion transmission rate is needed to promote its further application. Summary of the invention

[0006] In order to solve the above problems, the object of the present invention is to provide a carbon-coated lithium manganese iron phosphate nanomaterial and a preparation method thereof, so as to obtain a positive electrode material with higher specific capacity and better cycle stability.

[0007] One of the technical solutions of the present invention is to provide a carbon-coated lithium iron manganese phosphate nanomaterial, wherein the surface of the lithium iron manganese phosphate nanoparticles coated with the carbon layer also has a discontinuous polyanion sodium ion battery positive electrode material floating island structure, and the components of the floating island structure are one or more polyanion sodium ion battery positive electrode materials such as sodium vanadium phosphate, sodium vanadium oxyphosphate, sodium vanadium fluorophosphate, and sodium vanadium oxyphosphate, and the thickness of the floating island structure is 2-5nm. Polyanion-type sodium ion battery positive electrode materials and lithium iron manganese phosphate are both polyanion-type battery positive electrode materials. They can be directly and tightly combined with the surface of lithium iron manganese phosphate particles to form a lattice coherent structure. This type of sodium ion battery positive electrode material itself has good cycle stability and can inhibit the dissolution of Mn elements, thereby improving cycle stability; and it is a fast ion conductor structure with a faster lithium ion transmission network, which can accelerate the transmission rate of lithium ions during the charge and discharge process, thereby increasing its capacity; carbon itself has good electronic conductivity. In addition, its structure is loose and porous, and the electrolyte can be adsorbed on the surface of lithium iron manganese phosphate particles through capillary action to increase the lithium ion transmission rate. Therefore, the capacity decay of composite-coated lithium iron manganese phosphate during the cycle charge and discharge process is significantly slower than that of lithium iron manganese phosphate coated with ordinary carbon layer.

[0008] The second technical solution of the present invention is to provide a method for preparing a carbon-coated lithium manganese iron phosphate nanomaterial, the preparation method comprising the following steps:

[0009] Step 1, mixing a polyanion sodium ion battery positive electrode material precursor, an amorphous carbon source, a conductive carbon source, and a lithium iron manganese phosphate precursor to obtain a carbon-coated lithium iron manganese phosphate nanomaterial precursor;

[0010] Step 2: sintering the carbon-coated lithium manganese iron phosphate nanomaterial precursor obtained in step 1 at high temperature under a protective atmosphere, annealing and cooling to room temperature, and then grinding and sieving to obtain the carbon-coated lithium manganese iron phosphate nanomaterial.

[0011] The rough surface of lithium iron manganese phosphate formed during the high-temperature sintering process is easier to combine with the polyanion type sodium ion battery positive electrode material than the smooth surface of carbon. The polyanion type sodium ion battery positive electrode material has the same polyanion framework as lithium iron manganese phosphate. Therefore, during the high-temperature sintering process, it will directly form a lattice-coherent floating island structure on the rough surface of lithium iron manganese phosphate; at the same time, carbon is coated on the surface of the lithium iron manganese phosphate with the floating island structure during the high-temperature sintering process.

[0012] The positive electrode material of the polyanion sodium ion battery is one or more of sodium vanadium phosphate, sodium vanadium oxyphosphate, sodium vanadium fluorophosphate, and sodium vanadium oxyphosphate.

[0013] The polyanion sodium ion battery positive electrode material precursor is composed of vanadium pentoxide (V 2 O5 )Vanadium Phosphate (VPO 4 ) or vanadyl phosphate (VOPO 4 ) and other vanadium sources, sodium dihydrogen phosphate (NaH 2 PO 4 ) or sodium carbonate (Na 2 CO 3 ) and other sodium sources, diammonium phosphate (NH 4 H 2 PO 4 ) and other phosphorus sources, NaF and other fluorine sources, oxalic acid, citric acid and other carbon sources are mixed in the molar ratio of the final polyanion type sodium ion battery positive electrode material. For example, the sodium vanadium phosphate precursor is made of vanadium pentoxide (V 2 O 5 ), sodium dihydrogen phosphate (NaH 2 PO 4 ), oxalic acid and citric acid are mixed in a molar ratio of 1:3:6:4.

[0014] The amorphous carbon source refers to a substance containing carbon elements that can be used to prepare lithium manganese iron phosphate positive electrode materials and form an amorphous carbon layer, such as glucose, sucrose, citric acid, etc.

[0015] The conductive carbon source refers to a substance containing carbon elements that can be used to prepare lithium manganese iron phosphate positive electrode materials and form a conductive network, such as carbon nanotubes, acetylene black, Ketjen black, etc.

[0016] The mass of the polyanion sodium ion battery positive electrode material precursor is 5-11% of the mass of the lithium manganese iron phosphate precursor.

[0017] The mass of the amorphous carbon source is 3.0-10.0 wt % of the mass of the lithium manganese iron phosphate precursor, and preferably 5 wt %.

[0018] The mass of the conductive carbon source is 0.4-0.8 wt % of the mass of the lithium manganese iron phosphate precursor, and preferably 0.5-0.75 wt %.

[0019] The lithium manganese iron phosphate precursor is prepared by mixing a lithium source, a manganese source, an iron source and a phosphorus source in a molar ratio.

[0020] The mixing method comprises the following steps: ball milling the mixture in a ball milling aid at a rotation speed of 400-650 r / min for 4-10 hours, and then drying the mixture in a vacuum oven at 80-120° C. for 6-8 hours.

[0021] The protective atmosphere is at least one of argon, helium and nitrogen.

[0022] The high-temperature sintering temperature is 700-800° C., the heating rate is 3-5° C. / min, and the heat preservation time is 8-12 hours.

[0023] The beneficial results of the present invention are:

[0024] The lattice of the positive electrode material of the polyanion sodium ion battery is tightly integrated with the lattice of the lithium iron manganese phosphate particles, and it has good cycle stability itself, and can inhibit the dissolution of the Mn element, thereby improving the cycle stability; and its fast ion conductor structure has a faster lithium ion transmission network, which can accelerate the transmission rate of lithium ions during the charging and discharging process, thereby increasing its capacity; and carbon itself has good electronic conductivity. In addition, its structure is loose and porous, and it can adsorb the electrolyte on the surface of the lithium iron manganese phosphate particles through capillary action, thereby improving the lithium ion transmission efficiency.

[0025] The embodiment proves that the carbon layer coated polyanion type sodium ion battery positive electrode material @ lithium iron manganese phosphate prepared by the present invention has a retention rate of 97.15% relative to the maximum value of the specific capacity after 200 cycles, while the carbon layer coated lithium iron manganese phosphate has a retention rate of only 82.87% relative to the maximum value of the specific capacity after 200 cycles. The floating island type polyanion type sodium ion battery positive electrode material formed on the surface of lithium iron manganese phosphate, through close combination with the lithium iron manganese phosphate lattice, utilizes the excellent structural stability of the polyanion type sodium ion battery positive electrode material, stabilizes the lattice structure of the surface of lithium iron manganese phosphate, effectively improves the surface structure damage during the cycle and the poor cycle stability caused by Mn dissolution, and the capacity attenuation rate of the composite coated modified lithium iron manganese phosphate during the cycle charge and discharge process is significantly lower than that of the unmodified lithium iron manganese phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a high-resolution transmission electron microscope image of the sample in Example 1 of the present invention.

[0027] Figure 2 This is a scanning electron microscope image of the electrode after 200 cycles of 1C rate charge and discharge test at 25°C in Example 1 of the present invention.

[0028] Figure 3 This is a scanning electron microscope image of the electrode after 200 cycles of 1C rate charge and discharge test at 25°C for the comparative example of the present invention.

[0029] Figure 4 The capacity retention curves of Example 1, Example 2 and Comparative Example of the present invention before 200 cycles of 1C rate cycle charge and discharge test at 25°C. DETAILED DESCRIPTION

[0030] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0031] The raw materials used in the present invention, unless otherwise specified, are all conventional commercial products; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art. The technical scheme of the present invention is further described below through specific embodiments.

[0032] In the present invention, the substances that can be used to prepare the lithium manganese iron phosphate positive electrode material and form the amorphous carbon layer are common knowledge in the art, and generally include glucose, sucrose, citric acid, etc.;

[0033] The substances used to prepare lithium manganese iron phosphate positive electrode materials and form a conductive network are common knowledge in the art, and generally include carbon nanotubes, acetylene black, Ketjen black, graphene, and the like.

[0034] In the present invention, the protective atmosphere is common knowledge in the art, and is generally one or more of helium, argon, and nitrogen.

[0035] Example 1

[0036] The carbon-coated lithium iron manganese phosphate nanomaterial of this embodiment is prepared by mixing and sintering a sodium vanadium phosphate precursor, glucose, carbon nanotubes and a lithium iron manganese phosphate precursor, which are the positive electrode materials of a polyanion sodium ion battery. The specific preparation method is as follows:

[0037] Step 1: Mix vanadium pentoxide, sodium dihydrogen phosphate, oxalic acid and citric acid in a molar ratio of 1:3:6:4 and ball mill them in acetone as a ball milling aid at a speed of 650r / min for 4h. Place the ball-milled powder in a vacuum drying oven and dry it at 120°C for 6h to prepare a sodium vanadium phosphate precursor.

[0038] Lithium carbonate, iron phosphate, lithium dihydrogen phosphate, and manganese tetraoxide were mixed in a molar ratio of 1:2:3:1 and ball-milled in ethanol as a ball-milling aid at a speed of 600 r / min for 6 hours. The ball-milled powder was placed in a vacuum drying oven and dried at 80°C for 10 hours to prepare a lithium iron manganese phosphate precursor.

[0039] Weigh 0.1400g of sodium vanadium phosphate precursor, a positive electrode material for polyanionic sodium ion batteries, add 0.1000g of glucose, 0.0100g of carbon nanotubes, and 2g of lithium iron manganese phosphate precursor, grind in a mortar, and then ball mill in ethanol as a ball milling aid at 600r / min for 6h. Place the ball-milled powder in a vacuum drying oven and dry at 80°C for 10h. The positive electrode material for polyanionic sodium ion batteries and carbon-coated lithium iron manganese phosphate nanomaterial precursor can be obtained;

[0040] Step 2: Place the obtained polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial precursor in a tubular furnace and calcine under an argon atmosphere. The tubular furnace is heated at a rate of 5°C / min, the insulation temperature is 750°C, and the insulation time is 10 hours. After annealing and cooling to room temperature, the polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial can be obtained.

[0041] Figure 1 This is a high-resolution transmission electron microscope image of the sample in Example 1. The particles show two lattices with different orientations. The inner lattice is a lithium iron manganese phosphate phase, and the outer discontinuous floating island structure is a sodium vanadium phosphate phase with a thickness of about 2-5nm, indicating that a sodium vanadium phosphate floating island structure has been formed on the surface of the lithium iron manganese phosphate. The outermost amorphous coating layer of the particle is amorphous carbon.

[0042] Example 2

[0043] The carbon-coated lithium iron manganese phosphate nanomaterial of this embodiment is prepared by mixing and sintering a sodium vanadium phosphate precursor, glucose, carbon nanotubes and a lithium iron manganese phosphate precursor, which are the positive electrode materials of a polyanion sodium ion battery. The specific preparation method is as follows:

[0044] Step 1: Mix vanadium pentoxide, sodium dihydrogen phosphate, oxalic acid and citric acid in molar ratio and ball mill them in acetone at a speed of 650 r / min for 4 hours. Place the ball-milled powder in a vacuum drying oven and dry it at 120° C. for 6 hours to prepare a sodium vanadium phosphate precursor.

[0045] Lithium carbonate, iron phosphate, lithium dihydrogen phosphate, and manganese tetraoxide were mixed in a molar ratio of 1:2:3:1 and ball-milled in ethanol as a ball-milling aid at a speed of 600 r / min for 6 hours. The ball-milled powder was placed in a vacuum drying oven and dried at 80°C for 10 hours to prepare a lithium iron manganese phosphate precursor.

[0046] Weigh 0.1400g of sodium vanadium phosphate precursor, a positive electrode material for polyanionic sodium ion batteries, add 0.1000g of sucrose, 0.0150g of Ketjen black, and 2g of lithium iron manganese phosphate precursor, grind in a mortar, and then ball mill in ethanol as a ball milling aid at 600r / min for 6h. Place the ball-milled powder in a vacuum drying oven and dry at 80°C for 10h. The positive electrode material for polyanionic sodium ion batteries and carbon-coated lithium iron manganese phosphate nanomaterial precursor can be obtained;

[0047] Step 2: Place the obtained polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial precursor in a tubular furnace and calcine under an argon atmosphere. The tubular furnace is heated at a rate of 5°C / min, the insulation temperature is 800°C, and the insulation time is 8h. After annealing and cooling to room temperature, the polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial can be obtained.

[0048] The product of this example was analyzed by the same characterization method as in Example 1. The results showed that the particles had two lattices with different orientations. The inner lattice was lithium manganese iron phosphate phase, and the outer discontinuous floating island structure was sodium vanadium phosphate phase with a thickness of about 2-5 nm. The outermost amorphous coating layer of the particles was amorphous carbon.

[0049] Example 3

[0050] The carbon-coated lithium iron manganese phosphate nanomaterial of this embodiment is prepared by mixing and sintering sodium vanadium oxyphosphate precursor, a positive electrode material of a polyanion sodium ion battery, glucose, carbon nanotubes and a lithium iron manganese phosphate precursor. The specific preparation method is as follows:

[0051] Step 1: Mix vanadium pentoxide, sodium dihydrogen phosphate, sodium fluoride, oxalic acid and citric acid in molar ratio and ball mill them in acetone at a speed of 650 r / min for 4 hours. Place the ball-milled powder in a vacuum drying oven and dry it at 120°C for 6 hours to prepare a sodium vanadium phosphate precursor.

[0052] Lithium carbonate, iron phosphate, lithium dihydrogen phosphate, and manganese tetraoxide were mixed in a molar ratio of 1:2:3:1 and ball-milled in ethanol as a ball-milling aid at a speed of 600 r / min for 6 hours. The ball-milled powder was placed in a vacuum drying oven and dried at 80°C for 10 hours to prepare a lithium iron manganese phosphate precursor.

[0053] Weigh 0.1400g of sodium vanadium oxyphosphate precursor, a positive electrode material for polyanionic sodium ion batteries, add 0.1000g of sucrose, 0.0150g of Ketjen black, and 2g of lithium iron manganese phosphate precursor, grind in a mortar, and then ball mill in ethanol as a ball milling aid at 600r / min for 6h. Place the ball-milled powder in a vacuum drying oven and dry at 80°C for 10h. The positive electrode material for polyanionic sodium ion batteries and carbon-coated lithium iron manganese phosphate nanomaterial precursor can be obtained;

[0054] Step 2: Place the obtained polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial precursor in a tubular furnace and calcine under an argon atmosphere. The tubular furnace is heated at a rate of 5°C / min, the insulation temperature is 800°C, and the insulation time is 8h. After annealing and cooling to room temperature, the polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial can be obtained.

[0055] The product of this example was analyzed by the same characterization method as in Example 2, and it was found that the product structure was similar. The outside of the lithium manganese iron phosphate was a polyanion sodium ion battery positive electrode material sodium vanadium phosphate with a floating island structure, and the outermost layer was an amorphous carbon layer.

[0056] Example 4

[0057] The carbon-coated lithium iron manganese phosphate nanomaterial of this embodiment is prepared by mixing and sintering a polyanion sodium ion battery positive electrode material sodium vanadium fluorophosphate precursor, glucose, carbon nanotubes and a lithium iron manganese phosphate precursor. The specific preparation method is as follows:

[0058] Step 1: Mix vanadium phosphate, vanadyl phosphate, sodium fluoride, sodium carbonate, oxalic acid and citric acid in molar ratio and ball mill them in acetone at a speed of 650r / min for 4h. Place the ball-milled powder in a vacuum drying oven and dry it at 120°C for 6h to prepare sodium vanadium fluorophosphate precursor.

[0059] Lithium carbonate, iron phosphate, lithium dihydrogen phosphate, and manganese tetraoxide were mixed in a molar ratio of 1:2:3:1 and ball-milled in ethanol as a ball-milling aid at a speed of 600 r / min for 6 hours. The ball-milled powder was placed in a vacuum drying oven and dried at 80°C for 10 hours to prepare a lithium iron manganese phosphate precursor.

[0060] Weigh 0.1400g of sodium vanadium fluorophosphate precursor, a positive electrode material for polyanionic sodium ion batteries, add 0.1000g of sucrose, 0.0150g of Ketjen black, and 2g of lithium iron manganese phosphate precursor, grind in a mortar, and then ball mill in ethanol as a ball milling aid at 600r / min for 6h. Place the ball-milled powder in a vacuum drying oven and dry at 80°C for 10h. The positive electrode material for polyanionic sodium ion batteries and carbon-coated lithium iron manganese phosphate nanomaterial precursor can be obtained;

[0061] Step 2: Place the obtained polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial precursor in a tubular furnace and calcine under an argon atmosphere. The tubular furnace is heated at a rate of 5°C / min, the insulation temperature is 800°C, and the insulation time is 8h. After annealing and cooling to room temperature, the polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial can be obtained.

[0062] The product of this example was analyzed by the same characterization method as in Example 2, and it was found that the product structure was similar. The outside of the lithium manganese iron phosphate was a polyanion sodium ion battery positive electrode material sodium vanadium fluorophosphate with a floating island structure, and the outermost layer was an amorphous carbon layer.

[0063] Example 5

[0064] The carbon-coated lithium iron manganese phosphate nanomaterial of this embodiment is prepared by mixing and sintering a polyanion sodium ion battery positive electrode material sodium vanadium oxyfluoride phosphate precursor, glucose, carbon nanotubes and a lithium iron manganese phosphate precursor. The specific preparation method is as follows:

[0065] Step 1: Mix vanadium phosphate, vanadyl phosphate, sodium fluoride, sodium carbonate, oxalic acid and citric acid in molar ratio and ball mill them in acetone as a ball milling aid at 650 r / min for 4 hours. Place the ball-milled powder in a vacuum drying oven and dry it at 120°C for 6 hours to prepare sodium vanadium fluoride oxyphosphate precursor.

[0066] Lithium carbonate, iron phosphate, lithium dihydrogen phosphate, and manganese tetraoxide were mixed in a molar ratio of 1:2:3:1 and ball-milled in ethanol as a ball-milling aid at a speed of 600 r / min for 6 hours. The ball-milled powder was placed in a vacuum drying oven and dried at 80°C for 10 hours to prepare a lithium iron manganese phosphate precursor.

[0067] Weigh 0.1400g of sodium vanadium fluoride oxyphosphate precursor, a positive electrode material for polyanionic sodium ion batteries, add 0.1000g of sucrose, 0.0150g of Ketjen black, and 2g of lithium iron manganese phosphate precursor, grind in a mortar, and then ball mill in ethanol as a ball milling aid at 600r / min for 6h. Place the ball-milled powder in a vacuum drying oven and dry at 80°C for 10h. The positive electrode material for polyanionic sodium ion batteries and carbon-coated lithium iron manganese phosphate nanomaterial precursor can be obtained;

[0068] Step 2: Place the obtained polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial precursor in a tubular furnace and calcine under an argon atmosphere. The tubular furnace is heated at a rate of 5°C / min, the insulation temperature is 800°C, and the insulation time is 8h. After annealing and cooling to room temperature, the polyanion type sodium ion battery cathode material and carbon-coated lithium manganese iron phosphate nanomaterial can be obtained.

[0069] The product of this example was analyzed by the same characterization method as in Example 2, and it was found that the product structure was similar. The exterior of the lithium manganese iron phosphate was a polyanion sodium ion battery positive electrode material sodium vanadium fluoride oxyphosphate with a floating island structure, and the outermost layer was an amorphous carbon layer.

[0070] Comparative Example

[0071] This comparative example provides a carbon-coated lithium iron manganese phosphate nanomaterial, which is prepared by mixing and sintering a lithium iron manganese phosphate precursor, glucose, and carbon nanotubes. The specific preparation method is as follows:

[0072] Step 1: Lithium carbonate, iron phosphate, lithium dihydrogen phosphate, and manganese tetraoxide were mixed in a molar ratio of 1:2:3:1 and ball-milled in ethanol as a ball-milling aid at a speed of 600 r / min for 6 hours. The ball-milled powder was placed in a vacuum drying oven and dried at 80°C for 10 hours to prepare a lithium iron manganese phosphate precursor.

[0073] Weigh 0.1000g of glucose, add 0.0100g of carbon nanotubes, add 2g of lithium manganese iron phosphate precursor, grind in a mortar, and then ball mill in ethanol as a ball milling aid at 600r / min for 6h. Place the ball-milled powder in a vacuum drying oven and dry at 80°C for 10h. The carbon-coated lithium manganese iron phosphate cathode material precursor can be obtained;

[0074] Step 2: Place the obtained carbon-coated lithium manganese iron phosphate cathode material precursor in a tubular furnace and calcine it under an argon atmosphere. The heating rate of the tubular furnace is 5°C / min, the insulation temperature is 750°C, the insulation time is 10h, and then annealing and cooling to room temperature to obtain the carbon-coated lithium manganese iron phosphate cathode material.

[0075] Figure 2 and Figure 3 The scanning electron microscope images of the pole pieces of Example 1 and the comparative example after 200 cycles of 1C rate charge and discharge test at 25°C are shown respectively. Deep cracks appeared on the pole piece surface of the comparative example after the cycle, which would increase the contact area between the active material and the electrolyte, thereby causing more side reactions and reducing stability. However, due to the stable lattice structure of sodium vanadium phosphate coated on the surface of Example 1, the structural stability during the cycle was effectively improved and the microstress between the lithium manganese iron phosphate particles during the charge and discharge process was alleviated, which would not cause particle dissolution and the generation of microcracks between particles, so this phenomenon did not occur.

[0076] Figure 4 The capacity retention curves of the samples of Example 1, Example 2 and the comparative example in the cyclic charge and discharge test at 25°C and 1C rate are shown. The composite coated modified lithium manganese iron phosphate of Example 1 has a retention rate of 97.15% relative to the maximum value of the specific capacity after 200 cycles, and the composite coated modified lithium manganese iron phosphate of Example 2 has a retention rate of 95.48% relative to the maximum value of the specific capacity after 200 cycles. The carbon-coated lithium manganese iron phosphate of the comparative example has a retention rate of only 82.87% relative to the maximum value of the specific capacity after 200 cycles. This is mainly due to the floating island-type sodium vanadium phosphate formed on the surface of lithium manganese iron phosphate in Example 1 and Example 2. Through the close combination with the lithium manganese iron phosphate lattice, the excellent structural stability of sodium vanadium phosphate is used to stabilize the lattice structure of the surface of lithium manganese iron phosphate, and the surface structure damage and Mn dissolution phenomenon during the cycle process are effectively improved. The cycle performance attenuation caused by the phenomenon, so the composite coated modified lithium manganese iron phosphate has a significantly lower capacity attenuation rate than the unmodified lithium manganese iron phosphate during the cyclic charge and discharge process.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A carbon-coated lithium manganese iron phosphate nanomaterial, characterized in that: The surface of lithium manganese iron phosphate nanoparticles has a discontinuous floating island structure; The floating island structure is a polyanion sodium ion battery positive electrode material, and the thickness of the floating island structure is 2-5nm.

2. The carbon-coated lithium manganese iron phosphate nanomaterial according to claim 1, characterized in that: The positive electrode material of the polyanion sodium ion battery is one of sodium vanadium phosphate, sodium vanadium oxyphosphate, sodium vanadium fluorophosphate, and sodium vanadium oxyphosphate.

3. A method for preparing a carbon-coated lithium manganese iron phosphate nanomaterial, characterized in that: The steps include: Step 1, mixing a polyanion sodium ion battery positive electrode material precursor, an amorphous carbon source, a conductive carbon source, and a lithium iron manganese phosphate precursor to obtain a lithium iron manganese phosphate nanomaterial precursor; Step 2: sintering the lithium manganese iron phosphate nanomaterial precursor obtained in step 1 at high temperature under a protective atmosphere, annealing and cooling to room temperature, and then grinding and sieving to obtain the carbon-coated lithium manganese iron phosphate nanomaterial.

4. The method for preparing the carbon-coated lithium manganese iron phosphate nanomaterial according to claim 3, characterized in that: In step 1, the polyanion sodium ion battery positive electrode material precursor is one of a sodium vanadium phosphate precursor, a sodium vanadium oxyphosphate precursor, a sodium vanadium fluorophosphate precursor, and a sodium vanadium oxyphosphate precursor.

5. The method for preparing the carbon-coated lithium manganese iron phosphate nanomaterial according to claim 3, characterized in that: The mass of the amorphous carbon source is 5wt% of the mass of the lithium iron manganese phosphate precursor; the mass of the conductive carbon source is 0.5-0.75wt% of the mass of the lithium iron manganese phosphate precursor.

6. The method for preparing the carbon-coated lithium manganese iron phosphate nanomaterial according to claim 3, characterized in that: In step 1, the mass of the polyanion sodium ion battery positive electrode material precursor is 7% of the mass of the lithium manganese iron phosphate precursor.

7. The method for preparing the carbon-coated lithium manganese iron phosphate nanomaterial according to claim 3, characterized in that: The lithium manganese iron phosphate precursor in step 1 is prepared by mixing a lithium source, a manganese source, an iron source and a phosphorus source in a molar ratio.

8. The method for preparing the carbon-coated lithium manganese iron phosphate nanomaterial according to claim 3, characterized in that: The mixing method in step 1 is to ball mill in a ball milling aid at a speed of 600 r / min for 6 hours, and then dry in a vacuum oven at 80° C. for 10 hours.

9. The method for preparing the carbon-coated lithium manganese iron phosphate nanomaterial according to claim 3, characterized in that: The high temperature sintering temperature in step 2 is 750-800° C., the heating rate is 3-5° C. / min, and the insulation time is 8-10 hours.

10. Use of the carbon-coated lithium manganese iron phosphate nanomaterial as claimed in claim 1 as a positive electrode material for a lithium battery.